Phytochemical Screening And Anticancer Efficacy Of Boerhavia Diffusa: A Study In Hepatocellular Carcinoma-Induced Rat Model - Krishnamoorthy, Sridhar; Kalaivannan. J, Kalaivannan. J; Kaliyaperumal, Santhini Arulselvi; Prabhu K, Prabhu K; Kavimani M, Kavimani M; Shanthi B, Shanthi B; Kumar G, Mohan; Sivanesh M, Sivanesh M (Journal of Neonatal Surgery, 2025)
Background: This study aims to investigate the phytochemical composition, antioxidant and anticancer activity of Boerhavia diffusa extract in rats with hepatocellular carcinoma. Methods: To identify the essential bioactive components Boerhavia diffusa leaves were extracted using ethanol and subjected to GC-MS analysis. In male Sprague Dawley rats, hepatocellular cancer was induced with diethylnitrosamine and then with phenobarbitone. Boerhavia diffusa extract was administered to the induced rats with low dose (250 mg/kg) and high dose (500 mg/kg). Superoxide dismutase and catalase was measured to evaluate the antioxidant activity. Anticancer efficacy was measured by the changes in alpha-fetoprotein, white blood cells, haemoglobin, red blood cells and histopathological analysis of liver. GC-MS analysis confirmed the ethanolic extract of Boerhavia diffusa contained phytoconstituents like vitamin E, phytol and β-sitosterol. Results: Hemoglobin, WBC and RBC were significantly decreased in DEN induced group and recovered in extract administered group. The treated groups showed significantly higher levels of antioxidant enzyme activity, particularly CAT (1.49±0.092) and SOD (0.15±0.001), suggesting increased oxidative defense. Higher alpha-fetoprotein levels (6.97±0.623 ng/ml) were found in the carcinoma induced group and considerably lower level (4.43±0.521 ng/ml) was observed following the extract administration. Microscopic examination of the liver revealed restoration of hepatocytes in treated rats with less inflammation and reduced necrosis. Conclusion: This research suggests that the ethanolic extract of Boerhavia diffusa reveals notable antioxidant and anticancer properties, indicating its potential as a treatment for hepatocellular carcinoma. Boerhavia diffusa was used in traditional medicine for liver diseases, have scientific evidence by the presence of bioactive phytochemicals.